Festival Fun Fair in Full - Unknown (Evening News)
The picture showed that the Festival of Britain Battersea Park (London) fun fair was full on May 12, the first day of the Whitsun holiday. Fifteen thousand people were present and at one time there was a queue of 2,000 waiting to enter.
Keywords: Exhibitions -- Great Britain; Steel bands (Music) -- Great Britain; Steel band music -- Great Britain; Crowds -- Great Britain